Teaching Conservation of Natural Resources with Culturally Responsive and Context Specific Environment: The Stance of Cultro-Techno-Contextual Approach - Abolaji, Toyin Joy; Owolabi, Tunde; Lameed, Soladoye N.; Ogundowole, Ayodeji; Ige, Adeleke M.; Mustapha, Abiodun Gafar (FKIP - Universitas Riau, 2025)
A key reason for students' poor performance in biology is the lack of connection between their indigenous knowledge, cultural context, and local experiences and the subject's teaching. This study explored the efficacy of the culture-techno-contextual approach (CTCA) to enhance the achievement and attitudes of secondary school students in biology. A quasi-experimental group design was employed. The study involved 135 biology students from two intact classes in schools within an education district. The treatment group (CTCA) had 67 students and the control group had 70 students. The instruments used for data collection were the Conservation of Natural Resources Achievement Test (0.70) and the Conservation of Natural Resources Attitude Questionnaire (r= 0.78). Data were analyzed using MANCOVA, having satisfied the parametric assumptions. The findings revealed a statistically significant difference in the achievement and attitudes of students taught using the culture-techno-contextual approach compared to those in the control group (F = 16.87; p < 0.01). CTCA had no statistically significant impact on students in the experimental group based on gender (F = 16.87; p < 0.01). It was concluded that the CTCA is an effective tool for enhancing students' achievement and attitudes in biology.